2000
DOI: 10.1083/jcb.150.2.335
|View full text |Cite
|
Sign up to set email alerts
|

p38 Map Kinase Mediates Bax Translocation in Nitric Oxide–Induced Apoptosis in Neurons

Abstract: Nitric oxide is a chemical messenger implicated in neuronal damage associated with ischemia, neurodegenerative disease, and excitotoxicity. Excitotoxic injury leads to increased NO formation, as well as stimulation of the p38 mitogen-activated protein (MAP) kinase in neurons. In the present study, we determined if NO-induced cell death in neurons was dependent on p38 MAP kinase activity. Sodium nitroprusside (SNP), an NO donor, elevated caspase activity and induced death in human SH-SY5Y neuroblastoma cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
247
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(275 citation statements)
references
References 99 publications
27
247
1
Order By: Relevance
“…Moreover, experiments using antioxidants indicated that ROS act upstream of Bax relocalization and mitochondrial membrane depolarization (21). In this study, we provided further evidence that increased level of ROS induced by combination treatment with As 2 O 3 and phytosphingosine is essential for the p38 MAPK -mediated mitochondrial relocalization of Bax.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, experiments using antioxidants indicated that ROS act upstream of Bax relocalization and mitochondrial membrane depolarization (21). In this study, we provided further evidence that increased level of ROS induced by combination treatment with As 2 O 3 and phytosphingosine is essential for the p38 MAPK -mediated mitochondrial relocalization of Bax.…”
Section: Discussionsupporting
confidence: 55%
“…25 In a number of different cellular models, inhibition of both JNK and p38 prevented the translocation of Bax. [25][26][27] For peroxynitrite-induced apoptosis to occur, MLK, p38 and JNK had to be simultaneously activated, inducing Bax translocation to the mitochondria. Although it is not possible to causally relate the increased phosphorylation of mitochondrial JNK and the translocation of Bax to mitochondria, it is safe to say that both events are dependent upon the activation of MLK (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…24 Stimulated by death signals, the C-terminal domain of Bax changes its conformation and the C-terminal a-helix is removed from the BH3 domain, which allows the BH3 domain to interact with other antiapoptotic Bcl-2 family members. 27,28 Caspase 25 and p38 MAP kinase 29 may stimulate the translocation of Bax upon apoptotic stimulus. After Bax inserts into the mitochondrial membrane, Bax can directly induce the release of cytochrome c 30,31 or form permeability transition pore.…”
Section: Introductionmentioning
confidence: 99%